Estudo da seletividade das pescarias artesanais do camarão-da-amazônia - Macrobrachium amazonicum (HELLER, 1862) na baía do Guarujá, Pará, Brasil: subsídio à sustentabilidade pesqueira - CRESPIM, Renata da Costa e Silva (2019)
Fishery is commonly developed in the Amazon and has great importance as a source of protein and income generation for the local population. The estuaries of Pará State are biologically very productive and enable primary and secondary production, contributing to the shrimp’s development. The prawns Macrobrachium amazonicum species are often fished in the State of Pará, and your fishing is commonly performed with matapis (traps) that are made of strips of palm, providing a cylindrical shape. The bait called ' puqueca ' is often used for this type of fishing and can be made with lumps of boiled rice, babaçu or manioc flour, bits of fish or termite nests, wrapped in palm leaves. The presented work aims to contribute to the knowledge of the use of fishing gear with different dimensions in catching prawn Macrobrachium amazonicum in order to detect harmful fisheries, trying to propose solutions to more sustainable fisheries directed this feature.